High-glucose environment induced intracellular O-GlcNAc glycosylation and reduced galectin-7 expression in keratinocytes: Implications on impaired diabetic wound healing. Issue 2 (August 2017) - Huang, Shu-Mei; Wu, Ching-Shuang; Chiu, Min-Hsi; Yang, Hui-Jun; Chen, Gwo-Shing; Lan, Cheng-Che E.
Highlights: High glucose environment results in keratinocyte dysfunction and contributes to impaired wound healing in diabetics. Gene silencing of galactin 7 (Gal-7), a molecule essential for proper wound healing, reduced keratinocyte migration. High glucose environment increased intracellular O-glycosylation that contributed to reduction of Gal-7 in keratinocytes. Abstract: Background: Diabetes is an important global health issue due to its increasing prevalence and association with various complications. Impaired wound healing is a serious complication associated with diabetes that frequently results in infection and amputation. Galectin-7 (Gal-7) has been reported to play an important role during skin wound healing. Previously, we had demonstrated that high glucose environment alters physiologic functions of keratinocytes and contributes to impaired wound healing in diabetic condition. Objective: In this study, we hypothesized that Gal-7 expression of keratinocytes may be involved in delayed wound healing of diabetics. Methods: Using cultured human keratinocytes and diabetic mice model, the Gal-7 expression was evaluated under high glucose environment. Results: Our results demonstrated that high-glucose environment reduced Gal-7 expression, a molecule that plays an important role in keratinocyte migration. Additionally, we found that increased O -linked N-Acetyl-glucosamine ( O -GlcNAc) is responsible for reduced Gal-7 expression in keratinocytes exposed to high glucose environment. Conclusion: Taken together, restoring the levels of Gal-7 and O -GlcNAc glycosylation may present novel therapeutic approach to promote wound healing in diabetic patients.